Speech by Guest Speaker Prof. P. K. Nair during 3rd Graduation Ceremony - Nair, P. K. (University of Embu, 2018)
Speech by Guest Speaker Prof. P. K. Nair during 3rd Graduation Ceremony of University of Embu on Friday, 14th September, 2018